Determinants of using fixed-term contracts in the Egyptian labor market: Empirical evidence from manufacturing firms using world bank firm-level data for Egypt - Ahmed Fayez Abdelgouad (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
Based on dual labor market theory, fixed-term contracts (FTCs) as an important feature of labor market flexibility are analyzed to test the following hypothesis: Firms in the manufacturing sector in Egypt use FTCs to adjust the level of employment to the profit maximizing level in case of demand changes. The hypothesis is supported by the results of econometric analyses with a firmlevel data set from the World Bank Enterprise Surveys. Probit and Tobit models were used to estimate the probability and intensity of different kinds of numerical labor market flexibility (FTCs utilization, hiring and firing) in Egypt. Empirical results revealed that demand changes had no effects on using FTCs in the manufacturing firms in Egypt. In addition, the results indicated that there was no effect on using hiring and firing instruments.
Keywords: J21; J41; J42; 330; labor market flexibility; fixed-term contracts (FTCs); dual labor market